MATERIAL FLOW COST ACCOUNTING SEBAGAI UPAYA EFISIENSI BIAYA PRODUKSI KERUPUK IKAN ERNA JAYA - Azka, Aditya Fadillah; Agustine, Vinna Ayu; Nabiilah, Nabiilah; Syarif, Ahmad Maulana; Novita, Novita (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
The purpose of this research is to analyze whether the fish crackers in every production process Erna Jaya has generated material losses, in order to obtain transparent information on the effectiveness and efficiency of the use of raw materials and energy in the overall production process. Based on analysis of this study, it is suggested that the fish cracker factory Erna Jaya had material losses/waste in the production process by 15% derived from raw materials and energy is wasted. The results of this study provide a solution to improve production processes and recycle the waste generated as a production cost efficiency effort. As the ingredients and the dough is wasted and stuck to the production machine can be reused in the next production, a change of cooking oil on a regular basis, maintenance and engine maintenance by production personnel after each use, and can be sold as a raw material by a third party to increase income for the company.Keywords: raw material, energy, material losses, Material Flow Cost Accounting, production costs